Logical Fallacy Argumentation on Testimonials on Homeshopping Television Show - Syahyuni Srimayasandy (2021)
The decision to purchase a product is inseparable from the buyer's trust in a product. Testimonials are a tool for marketers to eliminate consumer barriers about the product to be purchased. Testimonials on home shopping television products tend to be controllable. The selection of sources, the use of scripts, and the editing process can be a form of media control over the information received by the public. This study focus on analyzing testimonials from the logical side of the testimony content. The method used to analyze this logical fallacy is qualitative content analysis. The text is separated using Toulmin's model into three parts, namely claim, ground, and warrant. This research uses a logical fallacy as a tool to evaluate the logic of the testimony in terms of content. The results of this study found that there was a logical fallacy in the testimony content. The fallacies include generalization fallacy, fallacy fallacies, fallacy of composition, appeal to wealth fallacy, appeal to pity, dan appeal to force.